COMPARISON OF THE EFFICACY OF TAZAROTENE 0.1% GEL WITH ADAPALENE 0.1% GEL IN THE TREATMENT OF FACIAL ACNE VULGARIS - Noor, Nasma; Paracha, Muhammad Majid; Kamal, Kashif; Muhammad Dawood; Sahibzada Mahmood Noor (Journal of Postgraduate Medical Institute, 2021)
Objective: To compare the efficacy of tazarotene 0.1% gel with adapalene 0.1% gel in the treatment of facial acne vulgaris. Methodology: This randomized control trial (RCT) was carried out from February to August 2019 in the Department of Dermatology, Lady Reading Hospital, Peshawar. A total of 106 Acne Vulgaris patients were enrolled in the study using non-probability consecutive sampling. A detailed history followed by through clinical examination was conducted for all patients. All patients were randomly allocated in two groups (Group A and Group B) by lottery method. In group A, patients were treated by topical tazarotene gel (0.1%) while the other group had topical adapalene gel (0.1%). Data was analyzed by SPSS version 22, descriptive and analytical statistics were applied where needed. Results: In present study, age of patients in Group A and B were 28±10.77 years and 30±11.12 years respectively. The male to female ratio in both groups was 1:1.5. In group A, topical tazarotene gel (0.1%) was effective in 72% of the cases whereas topical adapalene gel (0.1%) recorded effectiveness in 62% of cases (p-value=0.3017). Conclusion: We concluded that Tazarotene 0.1% gel is a more effective treatment option for facial acne vulgaris when compared with Adapalene 0.1% gel.